Self-Efficacy of Students as a Mediator between Entrepreneurial Learning Engagement and EFL Learners’ Performance towards Writing Skill - Akhter, Shamim; Lin, Chaohai; Guo, Feifei; Ahmed, Khalid (Journal of Posthumanism, 2025)
The current research is based on certain objectives with an inclination towards student performance. EFL learners based in China are required to learn English as a foreign language because they will have to interact with international communities in the future. Entrepreneurial activities require communication at a level that is easily understandable to all participants. This study is examining the correlation between ELE and SP to foster an entrepreneurial mindset among students. In addition, this study intends to examine the relationship between ELE and the SE and entrepreneurial competences of students. It strengthens the significance of entrepreneurial events theory by indicating that entrepreneurial learning engagement strongly supports students learning of entrepreneurship. It is an effective event in the entrepreneurial process. Therefore, the results strongly support the entrepreneurial events theory. Second, this study adds to the support of the theory of planned behavior. The results indicate that entrepreneurial learning engagement and its association with student’s self-efficacy and entrepreneurial competency are planned behaviors. Instructors should be clear about providing an engaging learning environment to students. Teachers should be self-efficacious and develop self-efficacy and competency in their learners. Moreover, this research implies that EFL learners can be good entrepreneurs as they will have more command of English than those who are not English language learners.